The excavation (Scottish Historical and Archaeological Internet Reports, 2005)
An account of the excavation methodology is presented along with the research goals, which of necessity, were formulated during the project as the discovery was unexpected. A description of the results of test pitting is followed by a phased archaeological description. The phases are as follows: phase 1 - features beneath the cairn; phase 2 - cultivation marks and preparation of the ground; phase 3 - the kerbed cairn, including its construction and subsequent adaptation with a number of sub-phases; phase 4 - post-cairn features which cut the cairn including postholes and field drains; phase 5 - a variety of unphased negative features of irregular shape, all located outwith the cairn.